Long-term CCN measurements at the central European ACTRIS research station Melpitz, Germany - Yuan Wang; Silvia Henning; Laurent Poulain; Frank Stratmann; Hartmut Herrmann; Alfred Wiedensohler (PANGAEA, 2021)
Long-term measurements on aerosol activation characteristics help to understand the aerosol indirect effects (AIEs) and narrow down the uncertainties of AIEs simulation; however, they are still scarce. Atmospheric aerosol measurements were conducted at the Melpitz observatory (51.53°N, 12.93°E, 86 m above sea level), 50 km to the northeast of Leipzig, Germany. The aerosol particles observed at Melpitz can be regarded as representative for the central European rural background conditions. The data was collected during 2012 to 2016, including the measurements of monodosperse CCN, particle number size distribution, and aerosol chemical composition, which was measured by DMT-CCNC, T-MPSS, and ACSM & MAAP.